Worldwide Prevalence of Intimate Partner Violence in Pregnancy. A Systematic Review and Meta-Analysis - Román-Gálvez, Rosario M.; Martín-Peláez, Sandra; Fernández-Félix, Borja M.; Zamora, Javier; Khan, Khalid S.; Bueno-Cavanillas, Aurora (Frontiers in Public Health, 2021)
Background: Intimate partner violence (IPV) affects outcomes of mothers and their offspring. This systematic review collated the worldwide literature on the rates of different types of IPV in pregnancy. Methods: Two reviewers independently identified cross sectional and cohort studies of IPV prevalence in pregnancy in online databases (PubMed, WOS and Scopus), selected and extracted data (participants' country, study quality, measurement tool (validation and purpose) and rates of IPV in pregnancy). We considered a high quality study if it had a prospective design, an adequate sampling method, a sample size estimation, a response rate >90%, a contemporary ascertainment of IPV in the index pregnancy, and a well-developed detailed IPV tool. We performed random effects meta-analysis and explored reasons for heterogeneity of rates. Results: One hundred fifty-five studies were included, of which 44 (28%) met two-thirds of the quality criteria. Worldwide prevalence of physical (126 studies, 220462 participants), psychological (113 studies, 189630 participants) and sexual (98 studies, 155324 participants) IPV in pregnancy was 9.2% (95% CI 7.7%-11.1%, I2 95.9%), 18.7% (15.1%-22.9%, I2 98.2%), 5.5% (4.0%-7.5%, I2 93.4%) respectively. Where several types of IPV were reported combined, the prevalence of any kind of IPV (118 studies, 124838 participants) was 25.0% (20.3%, 30.5%, I2 98.6%). IPV rates varied within and between continents, being the highest in Africa and the lowest in Europe (p<0.001). Rates also varied according to measurement purpose, being higher for diagnosis than for screening, in physical (p=0.022) and sexual (p=0.014) IPV. Conclusions: IPV prevalence in pregnancy varies across countries, with one-quarter of mothers exposed on average globally. Routine systematic antenatal detection should be applied worldwide.